2020
DOI: 10.3389/fneur.2020.00568
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Changes in Obsessive–Compulsive Disorder Correspond to Interference Control and Obsessions Severity

Abstract: Introduction: Deficits in neurocognitive mechanisms such as inhibition control and cognitive flexibility have been suggested to mediate the symptoms in obsessive-compulsive disorder (OCD). These mechanisms are proposedly controlled by the "affective" and "executive" orbitofronto-striato-thalamo-cortical (CSTC) circuits with well-documented morphological and functional alterations in OCD that are associated with OCD symptoms. The precuneus region has been suggested in OCD as another key structure associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 78 publications
(105 reference statements)
1
3
1
Order By: Relevance
“…Combined with the results mentioned above, the increased caudate connectivity may mainly originate from central CSTC structures (caudate) to the regions outside the CSTC loop. In accordance with recent evidence, increased connectivity between the caudate and regions outside the CSTC (e.g., the parieto-occipital cortex, the angular gyrus and dorsolateral prefrontal cortex) may counterbalance the disconnectivity of the traditional CSTC loops in OCD ( Fajnerova et al, 2020 ). Furthermore, the increased connectivity reported outside the CSTC (e.g., the frontal gyrus and temporal gyrus) could be related to visuo-spatial and sensory-motor processing, which may indirectly impact cognitive flexibility in OCD ( Wolff et al, 2017 ).…”
Section: Discussionsupporting
confidence: 88%
“…Combined with the results mentioned above, the increased caudate connectivity may mainly originate from central CSTC structures (caudate) to the regions outside the CSTC loop. In accordance with recent evidence, increased connectivity between the caudate and regions outside the CSTC (e.g., the parieto-occipital cortex, the angular gyrus and dorsolateral prefrontal cortex) may counterbalance the disconnectivity of the traditional CSTC loops in OCD ( Fajnerova et al, 2020 ). Furthermore, the increased connectivity reported outside the CSTC (e.g., the frontal gyrus and temporal gyrus) could be related to visuo-spatial and sensory-motor processing, which may indirectly impact cognitive flexibility in OCD ( Wolff et al, 2017 ).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, within the patient group, no significant performance differences were detected between patients who were classified as having either relatively mild or severe OCD symptoms. These results are unexpected and do not seem to support the view that impaired executive functioning is a core cognitive and pathophysiological feature of OCD (5)(6)(7)(8)(9). However, several factors partly related to limitations of the present study need to be considered before this conclusion can be well accepted.…”
Section: Discussioncontrasting
confidence: 85%
“…Studies have shown that patients with OCD typically perform more poorly than matched healthy control participants (HCs) on neuropsychological tests involving high-level cognitive or 'executive' functions, including planning, working memory, cognitive flexibility, and inhibitory motor control (5)(6)(7). These results have led to the hypothesis that impaired executive functioning (EF), including hyper excitability of the orbital frontal cortex and its functional connections, is a core cognitive and pathophysiological feature of OCD (8,9). Indeed, the current dominant view on the neuropathology of OCD focuses on abnormalities in prefrontal-striatal circuits implicated in EF (10).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hypoactivation in frontal lobe regions has been detected in patients with schizophrenia (SCZ) and major depressive disorder (MDD) during verbal fluency tasks when compared to their healthy counterparts [ 5 , 14 ]. Similarly, hyper- and hypo-connectivity between different brain regions during resting state have been identified in patients with schizophrenia (SCZ) [ 15 , 16 , 17 , 18 , 19 ] and major depressive disorder (MDD) [ 8 , 9 , 14 ], while decreased cerebral blood flow in bilateral symmetric regions of the inferior PFC has been detected in patients with obsessive compulsive disorder (OCD) when compared to their healthy counterparts [ 20 , 21 ]. PFC dysfunction in the form of hypo- or hyper-connectivity during resting state or hypoactivation during various cognitive tests (e.g., Stroop and verbal fluency test) has been extensively observed and reported in patient groups diagnosed with a variety of major neuropsychiatric disorders, which include SCZ, MDD, bipolar disorder (BD), post-traumatic stress disorder (PTSD), and attention deficiency and hyperactivity disorder (ADHD).…”
Section: Introductionmentioning
confidence: 99%